Awareness and knowledge of generation Z consumers about organic food in Serbia - Vehapi Semir; Mitić Sanja (Marketing (Beograd. 1991), 2023)
The aim of the research is to provide insight into the awareness and knowledge level of Generation Z regarding organic food and to assess their ability to recognize organic products in the Serbian market. For this study, a quantitative research approach was applied using a questionnaire filled out by 213 students from three universities in Serbia. The presented research results indicate insufficient familiarity with standards, certification, and labeling of organic products among Generation Z in Serbia. Out of the total number of participants aware of organic food, almost half do not know the exact definition of these products. Interestingly, occasional organic consumers are more familiar with the legal definition of organic food than regular organic consumers. The results also reveal that a significant portion of respondents do not distinguish between organic food on the one side and healthy and natural products on the other side. The confusion among Generation Z consumers is further confirmed by the finding that 37.2% of respondents do not recognize the national label for organic products in Serbia. The obtained findings can assist companies in developing effective marketing strategies to stimulate organic food consumption within the Generation Z market segment.